Spatial links. Production of sound art directed to the public space in a Latin American context - Duarte González, Irving (2022)
This paper took as its object of study the sound art works oriented at public spaces in Latin America, with the objective of studying their characteristics and determining whether this type of creative expressions has the ability to preserve and promote transversal identity traits to the Latin American region, a territory of big complexity and sociocultural diversity.For this, we proposed an analytical instrument that would allowed us to understand these productions from two angles: the link between the work and the space, classified as architectural, social and energetic, and the aesthetic approaches, which we analyze through narratives, resulting from the approach and relationship of a work with a specific site.As a result, we were able to find creative similarities between works from different latitudes, so it was possible to determine that they maintain a general base on an identity linked to the region. Specifically, we determined that one of the main characteristics, present in the analysis, was the interest assumed by this type of works in highlighting aspects of their contexts based on social elements, either from a political proposal or from awareness about the use of its spaces.